The Efficacy Of Detective Game On The Students Working Memory Capacity Among Selected Preschoolers In Hebei Province, China - Ji, Yuqing (2024)
Memory is an essential part of intelligence and various studies have shown that working memory is an even stronger predictor of academic success than intelligence. While parents recognize the importance of memory development, they are unclear with the children's memory development. This research involved the investigation of children’s memory improvement by using animation games. This research aims to determine the impact of different methods on children's interest in improving their memory, investigate the types of games that will enhance children's problem-solving, and examine those new games that will enhance children's memory. The research experiments are conducted in rural and urban public kindergartens in Shijiazhuang City, Hebei Province, China.This study utilize mixed method research design that involved observation method and real time interview method toward study groups. Thirty children are selected to participate in this experiment and divided into two groups, with each group consists of fifteen children respectively. The first group is trained with a picture book, while the second group is trained with an animated detective game. Each experiment is carried out once a week, and it takes four weeks to complete the entire experiment study. The results would determine the effectiveness of different games in term of attracting children's attention and improve children's memory. If the method of using animation games is effective in strengthening children's memory, it will provide another type of game guidance for preschool education, allowing for better ways of teaching.